Current Cost and ACRS Depreciation Expenses: A Comparison. - Stickney, Clyde P.; Mohr, Rosanne M.; Dilley, Steven C. (The Accounting Review, 1984)
ABSTRACT: Accounting policy makers and taxation authorities have been concerned with the understatement of depreciation expense that can accompany the use of generally accepted depreciation procedures. In addressing this concern, the taxation authorities have adopted a new method of historical cost depreciation known as the Accelerated Cost Recovery System (ACRS). Accounting policy makers, on the other hand, have addressed the "underdepreciation" issue with an experimental program of current cost depreciation disclosure. This paper presents a comparative analysis of the depreciation charges associated with the ACRS and current cost depreciation systems. The results of the analysis show that, for a variety of growth and price change conditions, the ACRS and current cost procedures can provide similar depreciation charges. As such, the ACRS techniques can alleviate considerably the "underdepreciation" effects that have been associated with some of the traditional historical cost depreciation methods.